Chemical Analysis of the Drug Mefenamic Acid in Herbal Medicine for Aches and Pains Komplit Sidomuncul UV-VIS Spectrophotometric Method - Arfinda Hanung Saputri; Bagus Made Virdiansyah; Habibah Inas Maulina (Asian Journal of Analytical Chemistry, 2023)
Jamu is a traditional medicine that is widely used by the community to prevent or help cure various diseases. There are many traditional medicines in Indonesia that do not contain chemicals. The mixing of BKO in herbal medicine is prohibited by the Indonesian government. Medicinal chemicals are medicinal chemical compounds that are intentionally added to herbal medicines with the aim of achieving the desired effect faster than usual. The medicinal chemical that is often added to jamu pegal linu is mefenamat acid. The purpose of this study is to analyze the BKO contained in jamu pegal linu "komplit sidomuncul". The parameters of the analysis method are linearity, limit of detection (LOD) and limit of quantitation (LOQ) using the Uv-Vis spectrophotometric method. The validation results of this method show that this method is good for detecting mefenamic acid in herbal medicine with a correlation coefficient (r) value of 0.9998; limit of detection (LOD) 0.073343 mg/L; limit of quantification (LOQ) 0.244476. In herbal medicine samples containing mefenamic acid 4.046 ppm shows a concentration above the LOD, meaning that mefenamic acid in the sample is detected.